MR-Guided Adaptive Radiotherapy for Bladder Cancer - Hijab, Adham; Tocco, Boris; Hanson, Ian; Meijer, Hanneke; Nyborg, Christina Junker; Bertelsen, Anders Smedegaard; Smeenk, Robert Jan; Smith, Gillian; Michalski, Jeff; Baumann, Brian C.; Hafeez, Shaista (Frontiers in Oncology, 2021)
Radiotherapy has an important role in the curative and palliative treatment settings for bladder cancer. As a target for radiotherapy the bladder presents a number of technical challenges. These include poor tumour visualisation and the variability in bladder size and position both between and during treatment delivery. Evidence favours use of magnetic resonance imaging (MRI) as an important means of tumour visualisation and local staging. The availability of hybrid systems incorporating both MRI scanning capabilities with the linear accelerator (MR-Linac) offers opportunity for in-room, real-time MRI scanning with ability of plan adaption at each fraction while the patient is on the treatment couch. This has a number of potential advantages for bladder cancer patients. In this article we examine the technical challenges of bladder radiotherapy and explore how magnetic resonance (MR) guided radiotherapy (MRgRT) could be leveraged with the aim of improving bladder cancer patient outcomes.